2018
DOI: 10.1002/ejoc.201800125
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Functionalization Reactions of Indole

Abstract: This review summarizes the progress achieved in the last fifteen years by application of homogeneous gold catalysis in the field of indole functionalization. Several electrophilic species obtained through gold‐catalyzed π‐activation have in fact been found to react with the nucleophilic positions of indole, thus allowing its efficient manipulation. In order to furnish a complete and clear overview on the role of the catalyst, the review is organized from the perspective of the gold‐activated substrate that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 165 publications
2
16
0
Order By: Relevance
“…To this end, the intermolecular hydroarylation of alkenes with indoles, as pioneered by M.-K. Wong and C.-M. Che, 18 was chosen. 19 In our previous study, MeDalphos gold( i ) chloride was shown to catalyze the hydroarylation of styrene to give indoles 13a,b and the role of the gold( i ) π-complex as key intermediate was supported. 10 Here, π-systems with distinct electronic properties, MA and NPM as electron-poor alkenes and DHP as electron-rich alkene, were tested ( Scheme 3 ).…”
Section: Resultsmentioning
confidence: 93%
“…To this end, the intermolecular hydroarylation of alkenes with indoles, as pioneered by M.-K. Wong and C.-M. Che, 18 was chosen. 19 In our previous study, MeDalphos gold( i ) chloride was shown to catalyze the hydroarylation of styrene to give indoles 13a,b and the role of the gold( i ) π-complex as key intermediate was supported. 10 Here, π-systems with distinct electronic properties, MA and NPM as electron-poor alkenes and DHP as electron-rich alkene, were tested ( Scheme 3 ).…”
Section: Resultsmentioning
confidence: 93%
“…Allenes figure among the most used electrophilic partners in gold catalysis, 44 and their reactions with indoles have been particularly studied 25 both in an inter-and intramolecular manner. With their axial chirality and various coordination modes, allenes have met particular success in enantioselective Au(I)-catalysis.…”
Section: Allenes and Related Unsaturated Functionsmentioning
confidence: 99%
“…This led to vibrant and intense creativity in the field of indole synthesis, 24 modification, functionalization, mostly because of the unique nucleophilicity of indoles combined with the ability of Au(I) complexes to activate a number of unsaturated bonds. 25 However, the ratio of enantioselective/non-enantioselective gold-catalyzed functionalization remains quite low, demonstrating that enantioselective gold-catalysis is still challenging in indole chemistry. In this review, we present the established results in the field of enantioselective indole functionalization, focusing on gold catalysis in order to highlight the strength and weaknesses of the area.…”
Section: Introductionmentioning
confidence: 99%
“…Because gold(III) is prone to be reduced, the majority of gold catalyzed transformations described so far involves gold(I) complexes. It has been evidenced that gold(I) is able to trigger the building of complex molecular frameworks in a few steps, under soft conditions and with a high degree of functional group tolerance [8][9][10][11][12][13][14][15]. Its special properties lay on relativistic effects, that contract its 6 s and 6p orbitals and expands the 5d shell, lowering the energy level of the LUMO which in turn is traduced in a high Lewis acidity [16].…”
Section: Introductionmentioning
confidence: 99%